What Keeps Filipinos Watching? The Role of Trust and Content Quality in Netflix Satisfaction - Eric S Parilla; Marc Edward Abadilla (Research Synergy Foundation, 2025)
The study investigates the impact of perceived trustworthiness and content quality on customer satisfaction within the OTT streaming service sector, specifically among Netflix subscribers in the Philippines. Using an entirely quantitative research approach, data were collected from a heterogeneous group of Filipino Netflix users, after which PLS-SEM was employed to analyze the strength and direction of relationships among key constructs. Dimensions such as reliability of services, data security, and authenticity were specified under perceived trustworthiness, while content quality dealt with variables including the number of options, cultural affinity, and high-quality productions. The findings indicate that consumer satisfaction is positively and significantly influenced by perceived trustworthiness and content quality. Indeed, trustworthiness stood out as a strong indicator of loyalty, implying that users develop an attachment to a service through secure and reliable service delivery. That content with a recognizable identity supports subscriber retention, keeping them interested in using the platform in the long run. Such findings extend the existing literature on OTT service adoption and retention by highlighting the need for a certain level of technical credibility and content value in emerging markets. In practical terms, it follows that OTT providers, such as Netflix, should adopt a mix of culturally aligned content strategies and transparent data practices to remain competitively viable. Whilst geographically angled towards the Philippines, its conceptual framework presents a replicable model for application in cross-cultural and international contexts. The study emphasizes the global significance of trust and content excellence in delivering an enhanced streaming experience within the rapidly expanding digital entertainment ecosystem worldwide.